Understanding How Habitat Conditions Modulate the Impact of Ecosystem Engineers on Tree-Hollow-Dwelling Organisms - Vergara-Egert, P; Fierro-Tapia, C; Alaniz-Baeza, A; Carvajal-Leon, M; Zuñiga-Alvarez, A (Elsevier B.V., 2024)
Saproxylophagous beetles usually are considered ecosystem engineers (EEs) by providing microhabitats for a great variety of organisms in tree hollows. However, there is still little clarity on the contribution of EEs to hollow-dwelling biodiversity since environmental conditions can exert control over the ecological function of EEs. We hypothesized that saproxylophages act as ecosystem engineers with community effects that are mediated by environmental forces over different spatiotemporal scales. Structural Equation Models (SEMs) were used to test this hypothesis against alternative hypotheses explaining the community structure of vertebrates and invertebrates occupying hollows in South American temperate forests. SEMs provided evidence for the interactive effects of saproxylophages and landscape-scale variables on invertebrates (fungivores, non-beetle predators, parasitoids, and detritivores) while predatory beetles were additively affected by saproxylophages. The abundance and richness of fungivores were positively affected by the richness of saproxylophages in landscapes with low cover of forests, while the abundance of saproxylophages affected positively the abundance of both parasitoids and non-beetle predators when secondary forests covered >30% of landscapes. The abundance and richness of vertebrates and invertebrates was also affected by habitat variables over different spatial scales. The small-sized saproxylophages played a more important role as EEs when compared to large-sized species while the most frequent species had effects comparable to those of the saproxylophagous assemblage. Our results suggest that the richness/abundance of EEs and landscape properties have compensatory and synergistic effects that lead to landscape-scale thresholds, thus providing insights into ecological conditions needed to conserve hollow-dwelling organisms. © 2023